MUC1 overexpression predicts worse survival in patients with non-small cell lung cancer: evidence from an updated meta-analysis - Huang, Xing (Oncotarget, 2017)
BACKGROUND: Previous studies on the prognostic role of MUC1 expression in non-small cell lung cancer (NSCLC) remain controversial. We conducted a meta-analysis to appraise the clinicopathological and prognostic effect of MUC1 in NSCLC patients. MATERIALS AND METHODS: Searches of PubMed, EMBASE and CNKI (Chinese National Knowledge Infrastructure) were conducted and relevant studies were extracted. The pooled hazard ratio (HR) or odds ratio (OR) with 95% confidence intervals (CIs) were used to estimate effects. Heterogeneity among studies and publication bias were also evaluated. RESULTS: A total of 15 studies with 1,682 patients were included in this meta-analysis. The pooled HRs indicated that elevated MUC1 expression was associated with poorer overall survival (HR = 2.12, 95% CI: 1.47–3.05; P < 0.001) and progression-free survival (HR = 2.00, 95% CI: 1.53-2.62; P < 0.001) in patients with NSCLC. Significant associations were also found in patients treated with epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) (HR = 3.16, 95% CI: 2.21–4.52, P < 0.001) and with a platinum-based regimen (HR = 4.35, 95% CI: 2.45–7.72, P < 0.001). Additionally, MUC1 overexpression was significantly associated with performance status (OR = 2.32, 95% CI: 1.13–4.73, P = 0.021). CONCLUSIONS: MUC1 could be a valuable biomarker of the prognoses of NSCLC patients.